GreenCut protein CPLD49 of Chlamydomonas reinhardtii associates with thylakoid membranes and is required for cytochrome b6f complex accumulation. (16th May 2018) - Wittkopp, Tyler M.; Saroussi, Shai; Yang, Wenqiang; Johnson, Xenie; Kim, Rick G.; Heinnickel, Mark L.; Russell, James J.; Phuthong, Witchukorn; Dent, Rachel M.; Broeckling, Corey D.; Peers, Graham; Lohr, Martin; et al.
Summary: The GreenCut encompasses a suite of nucleus‐encoded proteins with orthologs among green lineage organisms (plants, green algae), but that are absent or poorly conserved in non‐photosynthetic/heterotrophic organisms. In Chlamydomonas reinhardtii, CPLD49 (C onserved inP lantL ineage andD iatoms49 ) is an uncharacterized GreenCut protein that is critical for maintaining normal photosynthetic function. We demonstrate that a cpld49 mutant has impaired photoautotrophic growth under high‐light conditions. The mutant exhibits a nearly 90% reduction in the level of the cytochrome b 6 f complex (Cyt b 6 f ), which impacts linear and cyclic electron transport, but does not compromise the ability of the strain to perform state transitions. Furthermore, CPLD49 strongly associates with thylakoid membranes where it may be part of a membrane protein complex with another GreenCut protein, CPLD38; a mutant null for CPLD38 also impacts Cyt b 6 f complex accumulation. We investigated several potential functions of CPLD49, with some suggested by protein homology. Our findings are congruent with the hypothesis that CPLD38 and CPLD49 are part of a novel thylakoid membrane complex that primarily modulates accumulation, but also impacts the activity of the Cyt b 6 f complex. Based on motifs of CPLD49 and the activities of other CPLD49‐like proteins, we suggest a role for this putative dehydrogenase in the synthesis of a lipophilic thylakoid membrane molecule or cofactor that influences the assembly and activity of Cyt b 6 f . Significance Statement: Chlamydomonas GreenCut protein CPLD49 associates with thylakoid membranes, is required for normal photosynthetic activity and accumulation of the cytochrome b 6 f complex, and may interact with CPLD38, a green lineage‐conserved protein that is also required for normal cytochrome b 6 f complex accumulation.